2018
DOI: 10.1161/circulationaha.117.029535
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pediatric Medical Emergency Teams With Hospital Mortality

Abstract: Implementation of medical emergency teams in a large sample of pediatric hospitals in the United States was not associated with a reduction in hospital mortality beyond existing preimplementation trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Seventeen interventions involved the introduction of a new PTTT,13 15–18 60–72 one intervention introduced a mandatory triggering element to an existing PTTT71 and one study reported a large, multicentre analysis of MET introduction with no details on PTTT use 73. Twelve interventions included the introduction of a new MET or RRT,13 15–18 60–65 69 while four further interventions introduced a new PTTT in a hospital with an existing MET or RRT.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen interventions involved the introduction of a new PTTT,13 15–18 60–72 one intervention introduced a mandatory triggering element to an existing PTTT71 and one study reported a large, multicentre analysis of MET introduction with no details on PTTT use 73. Twelve interventions included the introduction of a new MET or RRT,13 15–18 60–65 69 while four further interventions introduced a new PTTT in a hospital with an existing MET or RRT.…”
Section: Resultsmentioning
confidence: 99%
“…In contradiction of the 'longer time to embed' hypothesis is a longitudinal time series with the introduction of paediatric Medical Emergency Teams in the USA. [25] There is no additional improvement in mortality or cardiac arrest over the baseline time trends. What isn't known about these centres is how well the early identi cation was developed and embedded.…”
Section: Discussionmentioning
confidence: 98%
“…[11,[57][58][59] Guidance on developing, implementing, evaluating and publishing complex interventions are available [13,59], but there are few actual case studies of implementing complex interventions in healthcare and relating to early warning systems. [60,61] The early warning or rapid response literature has focused broadly on 'does the score/response team work' [1,2,3,8,10] and, more recently, attempts to understand why the score/response team appears to work in single-centre studies and not large multi-centre studies [3,10,25,56,62,63]. It could be that the score/response team doesn't work or it could be that the implementation science is key.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, a prospective, multicenter trial examining deployment of a standardized pediatric rapid response team at four pediatric academic hospitals in Canada demonstrated a reduction in PICU mortality only after readmission, but no reduction in the rate of cardiopulmonary arrests or PICU mortality (20). Using the PHIS database, an interrupted time series analysis examined the effect of implementation of a rapid response team on annual risk-adjusted mortality rates at 38 freestanding pediatric hospitals and found no association with a reduction in hospital mortality (21).…”
Section: Moving the Patient Before They Code: Implementation Of Pediamentioning
confidence: 99%